Outcome and prognostic factors in pediatric malignant peripheral nerve sheath tumors: An analysis of the European Pediatric Soft Tissue Sarcoma Group (EpSSG) NRSTS‐2005 prospective study. Issue 10 (26th June 2019) - van Noesel, Max M.; Orbach, Daniel; Brennan, Bernadette; Kelsey, Anna; Zanetti, Ilaria; de Salvo, Gian Luca; Gaze, Mark N.; Craigie, Ross J.; McHugh, Kieran; Francotte, Nadine; Collini, Paola; Bisogno, Gianni; et al.
Abstract: Background: Malignant peripheral nerve sheath tumors (MPNST) are rare tumors of childhood. The role of standard chemotherapy in unresectable MPNST is still unclear. We report the outcome and prognostic factors in the EpSSG risk‐adapted prospective study for localized pediatric MPNST. Methods: Patients were stratified into four treatment groups defined by surgical resection, tumor size, and tumor grade (G): (a) surgery‐only group—resected tumors G1; (b) adjuvant radiotherapy group—R0/R1, G2 tumors; (c) adjuvant chemotherapy group—R0/R1, G3 tumors; and (d) neoadjuvant chemotherapy group—R2 resected tumors and/or nodal involvement. Chemotherapy consisted of four courses of ifosfamide‐doxorubicin and two courses of ifosfamide concomitant with radiotherapy (50.4‐54 Gy). Results: Overall, the study included 51 patients. The 5‐year event‐free survival (EFS) and overall survival (OS) were 52.9% (95% confidence interval, 38.1‐65.8) and 62.1% (46.7‐74.3), respectively. The 5‐year EFS was 92% (56.6‐98.9) for treatment group 1 ( N  = 13), 33% (0.9‐77.4) for treatment group 2 ( N  = 4), 29% (4.1‐61.2) for treatment group 3 ( N  = 7), and 42% (23.1‐60.1) for treatment group 4 ( N  = 27). Response rate to chemotherapy (partial response + complete response) in patients with measurable disease was 46%. The presence of neurofibromatosis type 1 (NF1; 51% of patients) was an independent poor prognostic factor for OS and EFS. Conclusion: The outcome for patients with resectable MPNST was excellent. Standard ifosfamide‐doxorubicin for unresectable MPNST rendered the best reported outcome. Children with NF1 disease seem to have worse prognosis.